Algorithmic Identity: Pinterest, Instagram, and the Practices of Curating the Visualization of Self - Raslene, Raslene; Widhiasih, Anggraeni (Indonesian Journal of Visual Culture, Design, and Cinema, 2026)
This research examines how Instagram and Pinterest shape users as creators, curators, and consumers of visual and textual content, influencing behaviors, preferences, and cultural identities. It explores how these platforms integrate images and texts into daily life, creating a "memory fabric" for branding and self-expression. Pinterest, focused on curated themes like decor, fashion, and beauty, has become a feminized space, while Instagram emphasizes image creation and sharing, with features like Stories and "Add Yours" encouraging participatory self-curation. The study analyzes how these platforms' algorithms and features shape visual preferences, self-representation, and cultural narratives. It highlights the cyclical maintenance of digital personas, including reinterpreting, renewing, and rewriting self-image, then connects these practices to broader themes of media materiality, cultural production, and pop culture. Using an interdisciplinary approach, the research investigates how digital archives, algorithms, and intermediality influence branding, aesthetics, and cultural memory in the current digital age.